2011
DOI: 10.1136/bmjqs.2010.047183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hospital-wide interventions to improve care for frail older inpatients: a systematic review

Abstract: No single best hospital-wide intervention could be identified using strict methodological criteria. However, several interventions had positive results, and may be used in hospital practice. Since strict methodological designs are not optimal for evaluating highly complex interventions and settings, the authors recommend studying hospital-wide interventions for older persons using adapted quality and research criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 52 publications
3
61
1
1
Order By: Relevance
“…These results were found by other scientific evidence, especially as we verified a prevalence ranging from 50% to 80% of frailty among hospitalized elderly [23][24][25] . The greater number and length of hospitalizations found in our research is also evidenced in other studies.…”
Section: Discussionsupporting
confidence: 76%
“…These results were found by other scientific evidence, especially as we verified a prevalence ranging from 50% to 80% of frailty among hospitalized elderly [23][24][25] . The greater number and length of hospitalizations found in our research is also evidenced in other studies.…”
Section: Discussionsupporting
confidence: 76%
“…Interventions such as cardiac rehabilitation, physical exercise, polypharmacy reduction (especially the reduction of unnecessary medications), nutritional recommendations, and HF self-care and treatment optimization could be particularly useful for delaying the transition from fragility to disability and for reducing mortality after discharge in frail patients 23, 24. Our study found a high prevalence of fragility in HFmrEF (48.6%); the prevalence was nearly as high as that found in HFpEF and slightly higher than that in HFrEF.…”
Section: Discussionmentioning
confidence: 99%
“…By using the prognosis-driven age cutoffs validated in this study, as opposed to subjective age cutoffs, clinical care pathways and research protocols have a better starting point to target the elderly patients who may benefit from preoperative comprehensive geriatric assessment and optimization. 24,25 …”
Section: Discussionmentioning
confidence: 99%